IMPLEMENTASI PERPRES NO. 95 TAHUN 2018 TENTANG SPBE TERHADAP PENERAPAN IDENTITAS KEPENDUDUKAN DIGITAL DI KABUPATEN SIDENRENG RAPPANG - Alya Alya; Andi Astinah Adnan; Muhammad Rais Rahmat R (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study aims to analyze the implementation of Presidential Regulation No. 95/2018 on the Electronic-Based Government System (SPBE), describe the implementation of the Digital Identity System (IKD) in Sidenreng Rappang Regency, and measure the impact of SPBE implementation on the adoption of IKD. The research was motivated by the low adoption rate of digital identity services despite the government’s continued efforts to accelerate the digital transformation of public services. This study employs a quantitative approach with a sample of 78 respondents selected through purposive sampling. Data were collected through structured questionnaires, field observations, and document reviews, then analyzed using descriptive statistics, validity tests, reliability tests, and simple linear regression with the assistance of SPSS 25.0. The results indicate that SPBE implementation falls into the “good” category at 64.71%, while IKD adoption falls into the “good” category at 65.00%. The regression analysis yielded a coefficient of determination of 0.552, indicating that the implementation of SPBE explains 55.2% of the variation in the application of IKD. The calculated t-value of 9.678 with a significance level of 0.000 proves the existence of a positive and significant effect of SPBE implementation on the application of IKD. The research findings confirm that strengthening the effectiveness of SPBE policies, particularly in the dimensions of resources, communication, and bureaucratic structure, becomes an important factor in supporting acceleration.